Pengaruh Penggunaan Teknologi dalam Pembelajaran Bahasa Indonesia terhadap Kemampuan Menulis Pada Siswa Kelas III SDI Betun Kota (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to determine the effect of technology use in Indonesian language learning on students' writing skills. The research method used was descriptive quantitative. This study was conducted at SDI Betun Kota, Wehali Village, Malaka Tengah District, Malaka Regency. The data collection technique used was a test, and the analysis technique used was a statistical t-test. The results showed that 18 students, or 44.44%, obtained high scores in writing skills, while 16.67% scored low in learning outcomes. This is evidenced by the results of the significance test, namely t-test of 14.52, which is greater than t-table at the 5% significance level. N = 18 (2.14), or equal to t-test > t-table, or 16.67 > 2.14. Based on the research results above, t-test is greater than t-table, with t-test = 16.67 and t-table = 2.14. Therefore, Ho is rejected and Ha is accepted. Thus, it can be concluded that technology use influences students' writing skills in Indonesian language learning in grade III of SDI Betun Kota.